Cochlear implantation in patients with Meniere's disease: A systematic review - Vincent M. Desiato (KeAi Communications Co., Ltd., 2021)
Background: Meniere's disease (MD) is an idiopathic disorder of the inner ear, which manifests as cochleo-vestibular dysfunction. Hearing loss will progress to a profound levelin a subset of patients with MD, and vestibular interventions can independently cause loss of hearing. The aim of this study was to systematically review the published literature describing the safety and efficacy of CI in patients with MD. Materials and methods: A systematic literature review was conducted in accordance PRISMA guidelines to identify articles that assessed at least one functional outcome in patients with MD who underwent CI. Demographic information, disease history, MD symptoms, outcomes measures, and complications related to CI were extracted from included studies. Results: In total, 17 studies were included, and 182 patients with MD underwent CI. The weighted-mean age was 61.9 years (range 27–85). Study objective and methodology varied, and there was significant heterogeneity in CI outcome measures reported. In total, 179 (98.3%) of 182 patients reported objective improvements in at least one hearing metric after CI. A total of 69 patients (37.9%) reported vertigo or severe dizziness prior to CI, compared to 22 patients (15.4%) postoperatively. Two studies reported significant reductions in postoperative Tinnitus Handicap Inventory score (THI). Quality of life assessments varied between studies. Complications rates were low with only nine patients (4.9%) reporting a serious CI-related complication. Conclusions: This systematic review evaluated 17 studies describing the safety and efficacy of CI in patients with MD and encountered many challenges due to small sample sizes, and heterogeneity in study design and outcomes measured. Despite these limitations, this study of 182 patients is to the best of our knowledge the largest systematic review evaluating the safety and efficacy of CI in MD. The results of this study support the need for a standardized approach to evaluating outcomes of CI in patients with MD in future studies.